Development Of Website-Based Learning Media Combined With Geogebra On Pythagoras Materials For VIII-Class Students Of Smp Negeri 1 Pasawahan, Kuningan District - Zahra , Nisrina Az; Cahdriyana, Rima Aksen (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to develop a website-based learning media on Pythagorean material. This study uses a development research method with the Research and Development (R&D) method with a 4D model (Define, Design, Development, and Dissemination. The research was carried out at SMP Negeri 1 Pasawahan Kuningan Regency  by dividing into two trials, namely 5 students for small class trials and 26 students for a large class trial. Instruments of the assessment used a questionnaire assessment of material experts, media experts and student responses. The results in this study were from material experts with an average of 3.71 categorized as very valid, from media experts with an average of 3.63 categorized as very valid and student responses in the interesting category with an average percentage of 77.23% so that the website-based learning media with Pythagorean material that the researcher developed is feasible to use in the learning process.